Keabsahan Status Wakaf Tanah Harta Bersama Tanpa Persetujuan Salah Satu Pihak Perspektif Hukum Islam: Studi Kasus Kecamatan Medan Amplas - Chairani Batubara, Dian Nur; Harahap, Abd. Rahman (Kamaya: Jurnal Ilmu Agama, 2025)
A husband or wife cannot take legal action against jointly owned property without the consent of each party, including in the case of donating jointly owned land. Because land acquired during the marriage period is a type of joint property. The aim of this research is to determine and analyze the validity of the waqf status of jointly owned land without the consent of one of the parties and the position of husband and wife as wakif in the waqf of land jointly owned by the late Muhammad Yusuf Harahap who donated a plot of land, which was then built on top of a mosque, namely the Nurul Iman mosque with proof of ownership certificate number 146, located in Timbang Deli sub-district, Medan Amplas District. However, the wife of the late Muhammad Yusuf Harahap, namely Mrs. Maimunah Dalimunthe, did not agree to the endowment and did not participate in ratifying the deed in lieu of the waqf pledge deed No. W.3/01/XI of 1993 before the official who made the land pledge deed for Medan Amplas sub-district. Of course this is contrary to law no. 1 of 1974 concerning marriage article 36 paragraph (1) concerning joint property, husband and wife can act with the consent of both parties. This research is based on field research with the approach used is descriptive-qualitative. The results of this research show that the validity of the waqf status of jointly owned land without the consent of one of the parties is not just a legal act that gives rise to legal consequences. But it is also an activity that originates from the law itself. In Islamic law, husband and wife have an equal position regarding joint assets, and decisions regarding these assets must be taken jointly. Waqf for joint assets must have the approval of both parties.